Aspects of the use of roboted systems for optimization of construction processes - Kulik, M.; Hrin, O.; Volkova, O. (Ways to Improve Construction Efficiency, 2019)
The article analyzes the relevance of using different types of robotized systems as a factor in improving the overall performance of technological operations involved in the implementation of construction processes. The variants of possible use of building robots are based on the analysis of the work of various scientists and materials from official sources of companies. The aforementioned binding to the possible massive introduction of robotic systems in the construction sector. The stated thoughts on the possible overcoming of problem on the introduction of robotic systems.